2010
DOI: 10.1007/s12170-010-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients, Weight Control, and Cardiovascular Health: A Systematic Review

Abstract: For some years, there has been interest in exploring the effects of high-fat and high-protein diets on the control of body weight. More recently, less extreme dieting paradigms have been studied, with a focus on the use of increased plant food components. This article reviews these diets from the standpoint of potential therapeutic use in cardiovascular risk reduction. We conducted a search of the literature published in 2008 and 2009 for studies assessing the effect of diet on body weight control, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The potential health benefits of dietary fiber have received considerable attention in recent years. Epidemiological and clinical studies have demonstrated that the consumption of dietary fiber is inversely related to the prevention of chronic diseases such as obesity, 2 type 2 diabetes, 3,4 cancer, 5,6 diarrhea, 7 and cardiovascular disease. 8 Fiber is often classified as either soluble dietary fiber (SDF) or insoluble dietary fiber (IDF).…”
Section: Introductionmentioning
confidence: 99%
“…The potential health benefits of dietary fiber have received considerable attention in recent years. Epidemiological and clinical studies have demonstrated that the consumption of dietary fiber is inversely related to the prevention of chronic diseases such as obesity, 2 type 2 diabetes, 3,4 cancer, 5,6 diarrhea, 7 and cardiovascular disease. 8 Fiber is often classified as either soluble dietary fiber (SDF) or insoluble dietary fiber (IDF).…”
Section: Introductionmentioning
confidence: 99%